The advantages of an ADHD classification from the perspective of teachers. Issue 5 (20th October 2019) - Wienen, Albert W.; Sluiter, Maruschka N.; Thoutenhoofd, Ernst; de Jonge, Peter; Batstra, Laura
ABSTRACT: In Western countries, the number of ADHD diagnoses and medical treatments of children has risen spectacularly over the last decennia, as has the amount of criticism about this trend. Various studies have shown that children receiving an ADHD classification often follow from initial signals that were raised in a school context. Hence, it becomes important to investigate precisely what advantages attach to ADHD classification in educational practice. In this qualitative study, 30 teachers were interviewed about their experiences and views of ADHD. The results suggest that a small number of interviewees sees no advantages to ADHD classification: the classification does not practically help them as teachers, they are familiar with the drawbacks of ADHD classification, and they take issue with the idea of labelling children. The greater number of interviewees, however, suggest ambivalence about ADHD classification: they are aware of its drawbacks while experiencing mainly advantages. According to the interviewees, ADHD classification explains undesirable behaviours and disappointing academic achievement. Classification thereby removes blame from pupils, parents and teachers, and so can be a starting point for productive agreement and collaboration. We will discuss the implications of these findings in the light of the concept of reification, child-centred problematisation and the development of more inclusive education.